2014
DOI: 10.3390/en7053179
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Cold Start of Proton Exchange Membrane Fuel Cells

Abstract: Successful and rapid startup of proton exchange membrane fuel cells (PEMFCs) at subfreezing temperatures (also called cold start) is of great importance for their commercialization in automotive and portable devices. In order to maintain good proton conductivity, the water content in the membrane must be kept at a certain level to ensure that the membrane remains fully hydrated. However, the water in the pores of the catalyst layer (CL), gas diffusion layer (GDL) and the membrane may freeze once the cell tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(36 citation statements)
references
References 104 publications
(171 reference statements)
1
34
0
Order By: Relevance
“…1,2 However, several improvements regarding degradation, performance, and cold start capability have to be achieved to ensure a reliable and durable operation even under extreme ambient operating conditions. 3 The cold start capability of fuel cells has been widely studied on lab-scale [4][5][6][7] as well as on technical fuel cells. 8,9 It has been reported that water does not deposit as ice inside fuel cells; it is produced in its supercooled aggregate state 4,5,7,10 and the phase transition to ice occurs randomly.…”
mentioning
confidence: 99%
“…1,2 However, several improvements regarding degradation, performance, and cold start capability have to be achieved to ensure a reliable and durable operation even under extreme ambient operating conditions. 3 The cold start capability of fuel cells has been widely studied on lab-scale [4][5][6][7] as well as on technical fuel cells. 8,9 It has been reported that water does not deposit as ice inside fuel cells; it is produced in its supercooled aggregate state 4,5,7,10 and the phase transition to ice occurs randomly.…”
mentioning
confidence: 99%
“…Concerning the aggregate state of water inside the electrode, contradictory findings have been published. Some studies 16,20,[26][27][28] claim that all product water produced during the start-up freezes inside the catalyst layer of the cathode. After filling a certain amount of the pore space with ice, the reactant gases are blocked, leading to a breakdown of the electrochemical reaction.…”
mentioning
confidence: 99%
“…19 Since ice preferentially forms at the interfaces between the CL, membrane, 3 diffusion media, 20 and pores/channels, 21 it can lead to delamination of the membrane from the CL, resulting in increased contact resistance. 22 The charge transfer resistance measured from AC impedance during a cold start from −10…”
mentioning
confidence: 99%